A high-temperature monoclinic bismuth phosphate nanocrystalline catalyst for photocatalytic production of hydrogen peroxide and its preparation

By controlling the temperature and pH value, high-temperature monoclinic phase bismuth phosphate nanocrystals were prepared, which solved the problem of low photocatalytic activity and achieved the effect of efficient photocatalytic production of hydrogen peroxide.

CN116332141BActive Publication Date: 2025-03-25JIANGNAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310064082.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-03-25
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

Among the existing methods of photocatalyzing hydrogen peroxide production, the photocatalytic activity of the high-temperature monoclinic phase bismuth phosphate is low and the electron and hole recombination rate is high, resulting in it not having high photocatalytic activity.

Method used

By controlling the temperature and pH, high-temperature monoclinic phase bismuth phosphate nanocrystals are prepared using anhydrous and oxygen-free device to form small-sized nanocrystals with more oxygen vacancies active sites, and their photocatalytic activity is improved.

Benefits of technology

High-efficiency photocatalytic hydrogen peroxide production of high-temperature monoclinic phase bismuth phosphate nanocrystals was achieved, with a yield of about 13mmol·L-1g-1h-1, surpassing previous reports.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116332141B_ABST
    Figure CN116332141B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-temperature monoclinic bismuth phosphate nanocrystalline catalyst for photocatalytic production of hydrogen peroxide and its preparation, belonging to the field of environmental science and inorganic material preparation. The present invention prepares a high-temperature monoclinic bismuth phosphate nanocrystalline photocatalyst with high-efficiency production activity of hydrogen peroxide by high-temperature pyrolysis, and the catalyst is a small particle with a particle size of 5-15nm, which has higher activity than the bismuth phosphate nanocrystals with a monoclinic monazite structure and the monoclinic bismuth phosphate synthesized by hydrothermal method. The present invention synthesizes bismuth phosphate nanocrystals with a high-temperature monoclinic phase for the first time, and applies it to the photocatalytic water and oxygen to directly generate hydrogen peroxide, which has higher photocatalytic activity than monoclinic monazite bismuth phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-temperature monoclinic bismuth phosphate nanocrystalline catalyst for photocatalytic production of hydrogen peroxide and a preparation method thereof, and belongs to the field of environmental science and inorganic material preparation. Background Art

[0002] As a green energy source, hydrogen peroxide (H2O2) is widely used in many fields such as chemical industry, biomedicine, and environmental protection. At present, the industrial production of H2O2 is mainly based on the anthraquinone method, but this method requires multiple steps of hydrogenation and oxidation reactions, consumes a lot of energy, and is not environmentally friendly; therefore, finding a low-energy, environmentally friendly H2O2 production method has received widespread attention.

[0003] Compared with the anthraquinone method, photocatalytic H2O2 production uses H2O and O2 as raw materials and semiconductor materials as photocatalysts, avoiding high-pressure reactions and the participation of hydrogen. In addition, there is no emission of benzene-containing pollutants during the production process, making it a safe and green production method. Currently, the photocatalysts that can directly synthesize hydrogen peroxide from water and oxygen are mainly organic photocatalysts, such as metal organic frameworks (Zn-based photocatalysts synthesized in US Patent US7008607B2). 2+ and metal organic frameworks with dihalides of terephthalic acid as ligands), organic polymers (photocatalyst RF resin synthesized by international patent WO2018074456 (A1)), etc. However, due to the disadvantage that organic photocatalysts themselves are unstable in high-concentration hydrogen peroxide, inorganic photocatalytic hydrogen peroxide production materials are in urgent need of development.

[0004] Bismuth phosphate is a new type of inorganic photocatalytic material with a non-metallic oxygen-containing acid salt structure. It has the characteristics of high photocatalytic activity and high stability. The phosphate ion structure is stable, the electron transfer speed is fast, the electron-hole recombination rate is low, and it is not easy to cause photocorrosion. There are three structures: hexagonal phase (HBIP), high-temperature monoclinic phase (mMBIP) and monoclinic phase monazite (nMBIP). It is one of the important directions of current photocatalytic material research. It is generally believed that the monoclinic phase monazite type (low-temperature monoclinic phase) has the highest photocatalytic activity, and its photocatalytic production of hydrogen peroxide has been reported (CN113231087A). There is no report on the production of hydrogen peroxide by high-temperature monoclinic phase bismuth phosphate, and because it is easier to form oxygen vacancies, resulting in a high recombination rate of electrons and holes, it is considered not to have high photocatalytic activity (C. Pan, et al., Catal. Sci. Technol., 2011, 1, 1399). However, oxygen vacancies are usually active sites for O2 reduction and H2O oxidation to generate hydrogen peroxide. How to retain as many oxygen vacancy active sites as possible while suppressing the recombination of electrons and holes is a challenge in developing efficient photocatalytic hydrogen peroxide production catalysts. Summary of the invention

[0005] In order to improve the photocatalytic activity of bismuth phosphate, one of the purposes of the present invention is to develop a method for synthesizing high-temperature monoclinic bismuth phosphate nanocrystals, comprising the following steps:

[0006] (1) mixing a bismuth salt, a phosphite compound, and a solvent, adjusting the pH to 0-3, and heating and mixing to obtain a solution A; then heating the solution A to 95-100° C. in an oxygen-free inert atmosphere and maintaining the temperature for 0.5-2 hours; then continuing to heat the solution to 250-350° C. and maintaining the temperature for 15-240 minutes to obtain a mixture B;

[0007] (2) The mixture B is cooled to room temperature, ethanol is added, and the mixture is centrifuged to obtain a solid phase, which is then washed with ethanol and cyclohexane and dried to obtain high-temperature monoclinic bismuth phosphate nanocrystals.

[0008] In one embodiment of the present invention, the pH in step (1) is preferably 0-1.

[0009] In one embodiment of the present invention, in step (1), solution A is obtained after heating and stirring at 60° C. for 12 hours.

[0010] In one embodiment of the present invention, in step (1), the bismuth salt is selected from any one or more of the following: bismuth sulfate, bismuth chloride, bismuth nitrate, or hydrates thereof, such as bismuth nitrate pentahydrate.

[0011] In one embodiment of the present invention, in step (1), the phospholipid compound is any one or more of the following: glycerol phosphate, bis(2-ethylhexyl) phosphate, trimethylol phosphate.

[0012] In one embodiment of the present invention, in step (1), the volume ratio of the phospholipid compound to the solvent is 1:(15-20), and can be specifically 1:19.

[0013] In one embodiment of the present invention, in step (1), the amount of bismuth salt added relative to the total amount of phospholipid compound and solvent is 10-30 mmoL / L, and specifically 12.5 mmoL / L.

[0014] In one embodiment of the present invention, in step (1), the solvent includes any one or more of: oleic acid, oleylamine.

[0015] In one embodiment of the present invention, in step (1), the solvent is oleic acid, oleylamine, or a mixed solution of oleic acid and oleylamine in different proportions, and the purity of oleic acid is analytical grade.

[0016] In one embodiment of the present invention, in step (1), the temperature is continued to be raised to 300° C. and maintained for 15 minutes to obtain a mixture B.

[0017] In one embodiment of the present invention, the steps are specifically included:

[0018] Preparation of bismuth salt solution A: Add 0.5 mmol of bismuth salt to the mixed solution of phospholipid, oleic acid and oleylamine to make the bismuth salt concentration 0.01-0.03 mol·L -1 , add 2-3 drops of phosphoric acid to make the pH of the solution about 1, and stir in a 60°C water bath for 12 hours to obtain solution A.

[0019] Synthesis of high-temperature monoclinic bismuth phosphate (mMBIP) nanocrystals: using a special anhydrous and oxygen-free device (double-row tube), solution A is placed in a three-necked flask and maintained at a constant temperature of 80°C with an electric heating jacket; first, the flask is evacuated with an oil pump, and then argon gas (purity ≥99.999%) is introduced into the flask to make the interior reach normal pressure (1-1.5atm), and the operation is repeated three times to remove oxygen in the flask; the temperature is raised to 100°C and maintained for 30 minutes to remove water from the solution; the temperature is slowly raised (about 5°C / min) to 250-350°C and maintained for 15-240 minutes; after the reaction is completed, a mixture B is obtained.

[0020] Collection of bismuth phosphate nanocrystals: After the mixture B is cooled to room temperature, an appropriate amount of ethanol is added, and the solid phase is obtained by centrifugation, and then washed with ethanol and cyclohexane until the supernatant is clear, and dried to obtain bismuth phosphate nanocrystals co-encapsulated with oleic acid and oleylamine. The centrifugal separation speed is 8000rpm, and the centrifugal time is 10min; the washing step is washed with 20-30mL ethanol and cyclohexane for 3-5 times; the drying condition is vacuum drying at 60℃ for 2h.

[0021] The present invention provides a high-temperature monoclinic bismuth phosphate nanocrystal based on the method.

[0022] The present invention also provides the use of the high-temperature monoclinic bismuth phosphate nanocrystals as a photocatalyst in catalyzing water and oxygen to produce hydrogen peroxide.

[0023] Beneficial effects:

[0024] Small-sized bismuth phosphate is currently mainly synthesized by hydrothermal method. Chinese patents CN110227517A and CN114772570A prepared bismuth phosphate nanospheres with particle sizes of 80-150nm and 20-33nm respectively by hydrothermal and calcination. Both bismuth phosphate nanocrystals have monoclinic monazite structures. The synthesis of high-temperature monoclinic bismuth phosphate (mMBIP) nanocrystals requires isolation of oxygen, higher temperatures and more acidic conditions, which may affect the degree of distortion of the tetrahedral structure of bismuth phosphate PO4, thereby forming different crystalline phases. Small-sized mMBIP nanocrystals can reduce the mean free path of electrons and accelerate the transfer of electrons by virtue of their small particle size; in addition, because they have more oxygen vacancy active sites, they can promote oxygen adsorption on the surface of the catalyst to react with water to directly generate hydrogen peroxide, further improving the performance of photocatalytic H2O2 production.

[0025] The main determinants of the synthesis of different crystalline phases of bismuth phosphate are the acidity of the solution and the temperature of the reaction. The synthesis of monoclinic monazite (low-temperature monoclinic phase) bismuth phosphate nanocrystals is a high-temperature hydrolysis reaction, which requires N2 protection (O2 content is less than 1%). At 190°C and without external acid, oleic acid is used as a capping agent, and the hydrolysis rate of the Bi-phospholipid complex is controlled by the kinetics of the reaction to produce small-sized nanocrystals (the average minimum size is about 8.3nm; C. Pan, et al., Size-controlled. J. Mater. Chem., 2011, 21, 4235). The synthesis of high-temperature monoclinic bismuth phosphate nanocrystals requires different conditions. The biggest difference is that high temperature is required to thermally decompose the Bi-phospholipid complex. By passing Ar, more stringent deoxygenation conditions (O2 content less than 0.1%) are achieved, so that the solvent can be raised to a higher temperature of 250°C-350°C without burning or exploding. In this case, the OC in the Bi-phospholipid complex is thermally unstable and will decompose. This process is controlled by thermodynamics. At the same time, oleic acid and oleylamine are required as end-capping agents to jointly inhibit the growth of crystal nuclei, which will form more, more uniform, and smaller crystal nuclei than the hydrolysis method. On this basis, the acidity of the solution is controlled by adding H3PO4. Only when the pH is less than 3 (the optimal pH is 0-1), smaller high-temperature monoclinic bismuth phosphate nanocrystals (the average minimum size is about 5.1nm) will be produced.

[0026] The present invention controls the temperature and pH value and uses an anhydrous and oxygen-free device to prepare small-sized bismuth phosphate nanocrystals with a high-temperature monoclinic phase, and the average minimum particle size of the nanocrystals is about 5.1 nm. In addition, the synthesized high-temperature monoclinic bismuth phosphate nanocrystals also have good photocatalytic H2O2 production performance (about 13 mmol·L -1 g -1 h -1 ), which has not been reported before. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 X-ray diffraction spectra of high-temperature monoclinic bismuth phosphate nanocrystals synthesized under different conditions;

[0028] Figure 2 The X-ray diffraction spectra of the monazite phase bismuth phosphate nanocrystals synthesized in Comparative Example 1 and the bulk bismuth phosphate in Comparative Example 2;

[0029] Figure 3 TEM images and particle size distribution diagrams of the high-temperature monoclinic bismuth phosphate nanocrystals synthesized in Example 1; wherein (a) is a morphology diagram of the synthesized high-temperature monoclinic bismuth phosphate nanocrystals, and (b) is a particle size distribution diagram thereof;

[0030] Figure 4This is a comparison chart of the photocatalytic production of H2O2 by the high-temperature monoclinic bismuth phosphate nanocrystals synthesized in Example 1, the monoclinic monazite bismuth phosphate nanocrystals synthesized in Comparative Example 1, and the bulk high-temperature monoclinic bismuth phosphate synthesized by hydrothermal synthesis in Comparative Example 3;

[0031] Figure 5 This is a diagram of multiple repeated tests on the photocatalytic preparation of hydrogen peroxide by high-temperature monoclinic bismuth phosphate nanocrystals synthesized in Example 1. DETAILED DESCRIPTION

[0032] Hydrogen peroxide concentration test method:

[0033] Potassium titanium oxalate solution and hydrogen peroxide form a yellow complex (yellow solution), and the absorbance is measured by an ultraviolet spectrophotometer, and the concentration of hydrogen peroxide is calculated by Lambert-Beer's law. Specifically, after 3 hours of reaction, 4 mL of the reaction solution is taken, the catalyst is filtered out using a 0.45 μm filter membrane, and then 1 mL of 0.02 M potassium titanium oxalate solution is added. The solution turns yellow, and the absorbance of the yellow solution is measured at 400 nm by an ultraviolet spectrophotometer to calculate the concentration of hydrogen peroxide.

[0034] Embodiment 1:

[0035] Synthesis of high temperature monoclinic bismuth phosphate nanocrystals (mMBIP nc):

[0036] 2mL of bis(2-ethylhexyl) phosphate and 38mL of oleic acid were added with 0.5mmoL of bismuth nitrate pentahydrate, the pH was adjusted to 1 with phosphoric acid, and the mixture was stirred in a 60°C water bath for 12h to obtain solution A; a special device for anhydrous and oxygen-free (double-row pipe) was used to place solution A in a three-necked flask, and the temperature was maintained at 80°C with an electric heating jacket; the flask was first evacuated with an oil pump, and then argon was introduced into the flask to make the internal pressure reach normal pressure, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100°C and maintained for 30min to remove water in the solution; the temperature was slowly raised (about 5°C / min) to 300°C and maintained for 15min; after the reaction was completed, a mixture B was obtained;

[0037] After the mixture B was cooled to room temperature, 40 mL of ethanol was added, and the solid phase was obtained by centrifugation, and then washed three times with 30 mL of ethanol and cyclohexane respectively. Finally, the solid C was obtained by vacuum drying at 60 ° C for 2 h. The full peak data fitting and comparison of the X-ray diffraction spectrum showed that the crystal phase of the product was mMBIP, that is, high-temperature monoclinic bismuth phosphate nanocrystals. The average particle size of the obtained high-temperature monoclinic bismuth phosphate nanocrystals was 5.1 nm.

[0038] Embodiment 2:

[0039] Synthesis of high temperature monoclinic bismuth phosphate nanocrystals:

[0040] 2 mL of bis(2-ethylhexyl) phosphate and 38 mL of oleic acid were added with 0.5 mmol of bismuth nitrate pentahydrate, the pH was adjusted to 1 with phosphoric acid, and the mixture was stirred in a 60°C water bath for 12 h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and the temperature was maintained at 80°C with an electric heating jacket; the flask was first evacuated with an oil pump, and then argon was introduced into the flask to make the internal pressure reach normal, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100°C and maintained for 3 hours. 0min to remove water from the solution; slowly increase the temperature (about 5℃ / min) to 350℃ and maintain for 15min; after the reaction is completed, a mixture B is obtained; after the mixture B is cooled to room temperature, 40mL of ethanol is added, and the solid phase is obtained by centrifugation, and then washed three times with 30mL of ethanol and cyclohexane respectively, and finally, the solid C is obtained by vacuum drying at 60℃ for 2h. The full peak data fitting and comparison are performed through the X-ray diffraction spectrum, and the crystalline phase of the product C is mMBIP, that is, high-temperature monoclinic bismuth phosphate nanocrystals.

[0041] Embodiment 3:

[0042] Synthesis of high temperature monoclinic bismuth phosphate nanocrystals:

[0043] 2 mL of bis(2-ethylhexyl) phosphate and 38 mL of oleic acid were added with 0.5 mmol of bismuth nitrate pentahydrate, the pH was adjusted to 1 with phosphoric acid, and the mixture was stirred in a 60°C water bath for 12 h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and the temperature was maintained at 80°C with an electric heating jacket; the flask was first evacuated with an oil pump, and then argon was introduced into the flask to make the internal pressure reach normal, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100°C and maintained for 3 hours. 0min to remove water from the solution; slowly increase the temperature (about 5℃ / min) to 270℃ and maintain for 240min; after the reaction is completed, a mixture B is obtained; after the mixture B is cooled to room temperature, 40mL of ethanol is added, and the solid phase is obtained by centrifugation, and then washed three times with 30mL of ethanol and cyclohexane respectively, and finally, the solid C is obtained by vacuum drying at 60℃ for 2h. The full peak data fitting and comparison are performed through the X-ray diffraction spectrum, and the crystalline phase of the product C is mMBIP, that is, high-temperature monoclinic bismuth phosphate nanocrystals.

[0044] Embodiment 4:

[0045] Synthesis of high temperature monoclinic bismuth phosphate nanocrystals:

[0046] 2mL of bis(2-ethylhexyl) phosphate and 38mL of oleylamine were added with 0.5mmol of bismuth nitrate pentahydrate, the pH was adjusted to 1 with phosphoric acid, and the mixture was stirred in a 60℃ water bath for 12h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and the temperature was maintained at 80℃ with an electric heating jacket; the flask was first evacuated with an oil pump, and then argon was introduced into the flask to make the internal pressure reach normal pressure, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100℃ and maintained for 3 hours. 0min to remove water from the solution; slowly increase the temperature (about 5℃ / min) to 300℃ and maintain for 15min; after the reaction is completed, a mixture B is obtained; after the mixture B is cooled to room temperature, 40mL of ethanol is added, and the solid phase is obtained by centrifugation, and then washed three times with 30mL of ethanol and cyclohexane respectively, and finally, the solid C is obtained by vacuum drying at 60℃ for 2h. The full peak data fitting and comparison are performed through the X-ray diffraction spectrum, and the crystalline phase of the product C is mMBIP, that is, high-temperature monoclinic bismuth phosphate nanocrystals.

[0047] Embodiment 5:

[0048] Synthesis of high temperature monoclinic bismuth phosphate nanocrystals:

[0049] 2 mL of bis(2-ethylhexyl) phosphate, 19 mL of oleylamine and 19 mL of oleic acid were uniformly mixed, 0.5 mmol of bismuth nitrate pentahydrate was added, the pH was adjusted to 1 with phosphoric acid, and the mixture was stirred in a 60°C water bath for 12 h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and the temperature was maintained at 80°C with an electric heating jacket; the flask was first evacuated with an oil pump, and then argon gas was introduced into the flask to make the internal pressure reach normal pressure, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 10 0℃, keep for 30min to remove water in the solution; slowly heat up (about 5℃ / min) to 300℃, keep for 15min; after the reaction is completed, a mixture B is obtained; after the mixture B is cooled to room temperature, 40mL of ethanol is added, centrifuged to obtain a solid phase, and then washed three times with 30mL of ethanol and cyclohexane respectively, finally, dried in vacuum at 60℃ for 2h to obtain a solid C, and the full peak data fitting and comparison are performed through the X-ray diffraction spectrum, and the crystalline phase of the product C is mMBIP, that is, high-temperature monoclinic bismuth phosphate nanocrystals.

[0050] Embodiment 6:

[0051] High temperature monoclinic bismuth phosphate nanocrystal photocatalytic H2O2 production experiment:

[0052] 5 mg of the high-temperature monoclinic bismuth phosphate nanocrystals obtained in Example 1-5 were mixed with 30 mL of deionized water, and ultrasonically dispersed for 5 min. Under 254 nm ultraviolet light irradiation, oxygen was continuously introduced and stirred for 3 h. After the reaction was completed, the oxygen introduction was stopped, the concentration of the hydrogen peroxide solution was measured, and the corresponding photocatalytic H2O2 yield was calculated. The specific conditions of the reaction were: light intensity 4 mW / cm 2 , oxygen flow rate 100mL / min, magnetic stirring speed 400rpm.

[0053] The results of photocatalytic H2O2 production of corresponding Examples 1-5 are shown in Table 1.

[0054] Table 1

[0055] catalyst Concentration of the obtained hydrogen peroxide solution (μM) <![CDATA[H2O2 production rate (mmol·L -1 g -1 h -1 )]]> Example 1 200 13.33 Example 2 176 11.73 Example 3 158 10.53 Example 4 23 2.53 Example 5 27 1.80

[0056] Embodiment 7:

[0057] Stability test: According to the method described in Example 6, the high-temperature monoclinic bismuth phosphate nanocrystals were subjected to the experiment repeatedly 10 times.

[0058] See the multiple repeated test diagrams of the photocatalytic preparation of hydrogen peroxide by high-temperature monoclinic bismuth phosphate nanocrystals coated with oleic acid provided in Example 1. Figure 5 As can be seen from the figure, the activity of high-temperature monoclinic bismuth phosphate nanocrystals decreased slightly in repeated experiments. This is because its small particle size caused partial agglomeration in repeated experiments, but it still has efficient photocatalytic performance in preparing hydrogen peroxide, and the performance remains stable (maintained at 80% after 10 repetitions).

[0059] Embodiment 8:

[0060] 2mL of bis(2-ethylhexyl) phosphate and 38mL of oleic acid were added with 0.5mmoL of bismuth nitrate pentahydrate without adding phosphoric acid. The pH of the solution was about 4 at this time. The mixture was stirred in a 60°C water bath for 12h to obtain solution A. Solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube) and maintained at a constant temperature of 80°C using an electric heating jacket. The flask was first evacuated with an oil pump, and then argon was introduced into the flask to make the internal pressure reach normal pressure. The operation was repeated three times to remove oxygen in the flask. The temperature was raised to 100°C. Maintain for 30 minutes to remove water from the solution; slowly increase the temperature (about 5°C / min) to 300°C and maintain for 15 minutes; after the reaction is completed, obtain a mixture B; wait for the mixture B to be cooled to room temperature, add 40 mL of ethanol, centrifuge to obtain a solid phase, and then wash it three times with 30 mL of ethanol and cyclohexane respectively, finally, vacuum dry at 60°C for 2 hours to obtain a solid C, and perform full peak data fitting and comparison through X-ray diffraction spectra. The crystalline phase of the product is nMBIP, and high-temperature monoclinic bismuth phosphate nanocrystals cannot be obtained.

[0061] Comparative Example 1:

[0062] Synthesis of monoclinic monazite structured nanocrystals (nMBIP nc):

[0063] 2mL of bis(2-ethylhexyl) phosphate and 38mL of oleic acid were uniformly mixed, 0.5mmoL of bismuth nitrate pentahydrate was added, and the mixture was stirred in a 60°C water bath for 12h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and a constant temperature of 80°C was maintained using an electric heating jacket; the flask was first evacuated with an oil pump, and then argon gas was passed into it to make the interior reach normal pressure, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100°C and maintained for 30min to remove water in the solution; the temperature was raised to 180°C and maintained for 2h; after the reaction was completed, a mixture B was obtained; after the mixture B was cooled to room temperature, 40mL of ethanol was added, and the solid phase was obtained by centrifugation, and then washed three times with 30mL of ethanol and cyclohexane respectively, and finally, the solid C was obtained by vacuum drying at 60°C for 2h, and the full peak data fitting and comparison were performed through the X-ray diffraction spectrum, and the crystal phase of the product C was nMBIP.

[0064] Application of monoclinic monazite nanocrystals in hydrogen peroxide production: 5 mg of catalyst was mixed with 30 mL of ultrapure water, ultrasonically dispersed for 5 min, and oxygen was continuously introduced into the mixture under 254 nm ultraviolet light irradiation and stirred for 3 h. After the reaction was completed, the oxygen introduction was stopped to obtain a hydrogen peroxide solution with a concentration of 65 μM. The specific conditions of the reaction were: light intensity 4 mW / cm 2 , the oxygen flow rate was 100 mL / min, and the magnetic stirring speed was 400 rpm.

[0065] Comparative Example 2:

[0066] Synthesis of monoclinic monazite structured nanocrystals (nMBIP nc):

[0067] 2mL of bis(2-ethylhexyl) phosphate and 38mL of oleylamine were uniformly mixed, 0.5mmoL of bismuth nitrate pentahydrate was added, and the mixture was stirred in a 60°C water bath for 12h to obtain solution A; solution A was placed in a three-necked flask using a special anhydrous and oxygen-free device (double-row tube), and a constant temperature of 80°C was maintained using an electric heating jacket; the flask was first evacuated with an oil pump, and then argon gas was passed into it to make the interior reach normal pressure, and the operation was repeated three times to remove oxygen in the flask; the temperature was raised to 100°C and maintained for 30min to remove water in the solution; the temperature was raised to 180°C and maintained for 2h; after the reaction was completed, a mixture B was obtained; after the mixture B was cooled to room temperature, 40mL of ethanol was added, and the solid phase was obtained by centrifugation, and then washed three times with 30mL of ethanol and cyclohexane respectively, and finally, the solid C was obtained by vacuum drying at 60°C for 2h, and the full peak data fitting and comparison were performed through the X-ray diffraction spectrum, and the crystal phase of the product C was nMBIP.

[0068] Application of monoclinic monazite nanocrystals in hydrogen peroxide production: 5 mg of catalyst was mixed with 30 mL of ultrapure water, ultrasonically dispersed for 5 min, and oxygen was continuously introduced into the mixture under 254 nm ultraviolet light irradiation and stirred for 3 h. After the reaction was completed, the oxygen introduction was stopped to obtain a hydrogen peroxide solution with a concentration of 18 μM. The specific conditions of the reaction were: light intensity 4 mW / cm 2 , the oxygen flow rate was 100 mL / min, and the magnetic stirring speed was 400 rpm.

[0069] The comparative results of the photocatalytic H2O2 production of the corresponding Examples 1, 4 and Comparative Examples 1, 2 are shown in Table 2.

[0070] Table 2

[0071]

[0072]

[0073] Comparative Example 3:

[0074] Synthesis of bulk high-temperature monoclinic bismuth phosphate (mMBIP-HT): Mix 30 mL of 16 mM phosphoric acid aqueous solution with 3 mmol of bismuth nitrate pentahydrate, and stir at 600 rpm for 30 min at room temperature to obtain a uniformly mixed solution A; transfer solution A to a 50 mL polytetrafluoroethylene-lined hydrothermal autoclave and hydroheat at 200°C for 72 h; after the hydrothermal reaction, cool to room temperature, centrifuge the product, and wash with deionized water until neutral; dry at 80°C for 12 h to obtain product B; perform full peak data fitting and comparison through X-ray diffraction spectrum, and the crystalline phase of product B is mMBIP.

[0075] Application of high-temperature monoclinic bismuth phosphate in the production of hydrogen peroxide: Referring to Example 6, a comparative experiment on the photocatalytic activity of high-temperature monoclinic bismuth phosphate was carried out under the same conditions. After the reaction was completed, a sample was taken and potassium titanium oxalate solution was added dropwise. No yellow solution was formed, and there was no obvious peak at 400nm on the ultraviolet spectrophotometer, indicating that the high-temperature monoclinic bismuth phosphate obtained by this method does not have the activity of photocatalytic production of H2O2.

Claims

1. A method for synthesizing high-temperature monoclinic bismuth phosphate nanocrystals, comprising the following steps: (1) mixing a bismuth salt, a phosphite compound, and a solvent, adjusting the pH to 0-3, and heating and mixing to obtain a solution A; then heating the solution A to 95-100° C. in an oxygen-free inert atmosphere and maintaining the temperature for 0.5-2 hours; then continuing to heat the solution to 250-350° C. and maintaining the temperature for 15-240 minutes to obtain a mixture B; (2) The mixture B is cooled to room temperature, ethanol is added, and the mixture is centrifuged to obtain a solid phase, which is then washed with ethanol and cyclohexane and dried to obtain high-temperature monoclinic bismuth phosphate nanocrystals.

2. The method according to claim 1, characterized in that The pH in step (1) is 0-1.

3. The method according to claim 1, characterized in that In step (1), the bismuth salt is selected from any one or more of the following: bismuth sulfate, bismuth chloride, bismuth nitrate, or a hydrate thereof.

4. The method according to claim 1, characterized in that: In step (1), the phospholipid compound is any one or more of the following: glycerol phosphate, bis(2-ethylhexyl) phosphate, and trimethylol phosphate.

5. The method according to claim 1, characterized in that In step (1), the volume ratio of the phospholipid compound to the solvent is 1:(15-20).

6. The method according to claim 1, characterized in that In step (1), the amount of bismuth salt added relative to the total amount of phospholipid compound and solvent is 10-30 mmol / L.

7. The method according to claim 1, characterized in that In step (1), the solvent includes any one or more of: oleic acid and oleylamine.

8. The method according to any one of claims 1 to 7, characterized in that: In step (1), the temperature is continued to be raised to 300° C. and maintained for 15 min to obtain a mixture B.

9. A high-temperature monoclinic bismuth phosphate nanocrystal prepared by the method described in any one of claims 1 to 8.

10. Use of the high-temperature monoclinic bismuth phosphate nanocrystals according to claim 9 as a photocatalyst in catalyzing water and oxygen to produce hydrogen peroxide.

Citation Information

Patent Citations

  • CuBi2O4 / BiPO4p-n heterojunction photocatalyst as well as preparation method and application thereof

    CN110227517A

  • Small-size bismuth phosphate, preparation method thereof, photocatalyst and application of photocatalyst

    CN114772570A

  • Process for preparing hydrogen peroxide from the elements

    US7008607B2

  • Method for producing hydrogen peroxide, kit for hydrogen peroxide production, organic polymer photocatalyst used in said method and kit, and method for producing said organic polymer photocatalyst

    WO2018074456A1

  • Novel compound sound catalyst mMBIP-MWCNT (Multi-walled carbon nanotubes)-In2O3 as well as preparation method and application thereof

    CN107597153A